Risiko Kesehatan Lingkungan Akibat Paparan Polusi Udara dan Dampaknya terhadap Kesehatan Manusia: Literatur Review - Analizza Ina Lea; Arini Novita Ati; Maurits R.L. Sjioen; Yulianti A Syarif Hadi; Luh Putu Ruliati (KOLONI, 2026)
Air pollution has become a major environmental health concern at both global and national levels due to its significant impact on human health. Exposure to pollutants such as PM2.5, PM10, and carbon monoxide (CO) has been associated with increased risks of respiratory and cardiovascular diseases, as well as premature mortality. This study aimed to synthesize scientific evidence on environmental health risks related to air pollution exposure and its impact on human health. An integrative literature review approach was conducted using 12 articles published between 2019 and 2024, retrieved from Google Scholar, PubMed, and ScienceDirect. Data were analyzed descriptively and narratively by examining study objectives, research design, key findings, and implications. The results indicate that most studies reported pollutant levels exceeding recommended standards, with Risk Quotient (RQ) values greater than 1, suggesting significant health risks. Vulnerable populations, including informal workers, urban communities, and industrial workers, were found to have higher exposure levels. Furthermore, a consistent association was identified between air pollution and respiratory diseases such as acute respiratory infections. Overall, air pollution is confirmed as a major environmental health risk, highlighting the need for comprehensive control strategies through environmental policies and public health interventions.